Hubungan Tingkat Pengetahuan Dengan Sikap Keluarga Penderita Demam Berdarah Dengue Tentang Pemberantasan Sarang Nyamuk (PSN) Di Wilayah Kerja Puskesmas Curahdam - Susanti, Riska Dewi Dian; Hefniy, Hefniy; Agustin, Yuana Dwi; Nugroho, Setyo Adi (Jurnal Keperawatan Profesional, 2021)
Dengue Hemorrhagic Fever (DHF) is also one of the infectious diseases that often cause extraordinary events. Low awareness to maintain environmental cleanliness and lack of public knowledge about eradicating mosquito nests to prevent Dengue Hemorrhagic Fever. This study aims to identify the relationship between the level of knowledge and the family attitudes of dengue hemorrhagic fever sufferers regarding the eradication of mosquito nests (PSN) in the work area of the Curahdami Health Center in Bondowoso Regency.Types of quantitative research designs. population and sample of 37 respondents by using total sampling. Data collection techniques used the Likert scale questionnaire to measure Knowledge Level and bivariate analysis was performed to determine the relationship between variables using Spearman's Rho. Statistical test results of Spearman's Rho. Obtained p-value 0.002 which means that Ho is rejected and H1 is accepted. There is a relationship between the level of knowledge with the family attitudes of dengue hemorrhagic fever sufferers about the eradication of mosquito nets in the work area of the bulk health center with a correlation coefficient of 0.487.From the results of this study, the level of knowledge of families suffering from dengue fever in eradicating mosquito nests in the Bondowoso district health center area is good.